Before- and after-school physical activity programs : frameworks, critical issues, and underserved populations - Marttinen, Risto; Centeio, Erin E.; Quarmby, Thomas (Abingdon, Oxon ; New York, NY : Routledge, 2021)
"This is the first book to offer a critical examination of the delivery of before and after-school physical activity programs, from global perspectives. It introduces key theory and best practice in before and after-school physical activity research and programming, and is an essential resource for educators involved in the design and implementation of after-school programs. With contributions from leading international researchers and practitioners in the field of health and physical education, the book provides an overview of research methods in before and after-school physical activity. It offers insight on theoretical frameworks and the implementation of programs as they relate to policy in schools, as well as an overview of social and emotional learning in after-school programs. The book also explores inclusive before and after-school physical activity programming for underserved communities, covering key topics from Positive Youth Development and urban programming to developing adult leaders and working with LGBTQI populations and children with disabilities. This book is important reading for researchers in health and physical education, and policy-makers, teachers, youth workers and coaches working with children in physical education, health education, physical activity or sport"--
OCLC-licensed vendor bibliographic record.
Keywords: Physical education for children; After-school programs; EDUCATION / Physical Education; SPORTS & RECREATION / General; Before school programs